Kualitas Terjemahan Subtitle Arab-Indonesia Pada Lagu Rahmatan Lil Alamin Menggunakan Google Translate Perspektif Nababan - sholehah, izzatus (Maliki Interdisciplinary Journal, 2025)
English abstract. This study examines the quality of the translation of the lyrics of the song entitled “Rahmatan Lil Alamin” from Arabic to Indonesian using Google Translate. This study was conducted because many people do not understand the message contained in the song, so they search for translations using translation tools without assessing the quality of the translation. In this case, the researcher used a descriptive qualitative method to examine the quality of the translation, and the research design used analytical research, data collection, identification, analysis, and then synthesis to provide an explanation of the concepts or events observed. The researcher used two methods to provide data, namely the observation method and the note-taking method. This study uses Nababan’s perspective theory, which observes the levels of accuracy and acceptability, which are divided into three categories: accurate, less accurate, inaccurate, acceptable, less acceptable, and unacceptable. The results of this study on the quality of the translation of the song “Rahmatan Lil Alamin” found 35 data points. In the Accurate category, there were 9 data points with a percentage of 15%, Less Accurate with 18 data points and a percentage of 75%, and Inaccurate with 8 data points and a percentage of 10%. Meanwhile, the Acceptable category had 24 data points with a percentage of 83%, Less Acceptable had 3 data points with a percentage of 4%, and Unacceptable had 8 data points with a percentage of 13%.